2015
DOI: 10.1111/maps.12453
|View full text |Cite
|
Sign up to set email alerts
|

Devolatilization or melting of carbonates at Meteor Crater, AZ?

Abstract: We have investigated the carbonates in the impact melts and in a monolithic clast of highly shocked Coconino sandstone of Meteor Crater, AZ to evaluate whether melting or devolatilization is the dominant response of carbonates during high-speed meteorite impact. Both melt-and clast-carbonates are calcites that have identical crystal habits and that contain anomalously high SiO 2 and Al 2 O 3 . Also, both calcite occurrences lack any meteoritic contamination, such as Fe or Ni, which is otherwise abundantly obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…However, Hörz et al. () found that calcite occurrences from Meteor Crater impactites have characteristics that are inconsistent with a melt origin and that the carbonate target was largely devolatilized. Carbonate melt was not produced in the shock experiments to 60 GPa documented here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Hörz et al. () found that calcite occurrences from Meteor Crater impactites have characteristics that are inconsistent with a melt origin and that the carbonate target was largely devolatilized. Carbonate melt was not produced in the shock experiments to 60 GPa documented here.…”
Section: Discussionmentioning
confidence: 99%
“…; Langenhorst and Deutsch ; Hörz et al. ). Early shock‐recovery experiments for calcite to quantify how much CO 2 is released at a given shock pressure yielded seemingly conflicting results: the experimental devolatilization studies of Boslough et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Hörz et al. ; Bell ). Although frequently studied in shock recovery experiments, no consensus has been reached so far regarding the onset or even nature of specific shock effects in carbonates.…”
Section: Open Issuesmentioning
confidence: 99%
“…More generally, the role of melting and devolatilization has been discussed and debated by Osinski et al (2008), Hörz et al (2015), and Bell (2016). Howard (2011) invoked volatiles in the shallow crust to enhance the dispersal of impact melts as tektites.…”
Section: Related Resourcesmentioning
confidence: 99%